Produção de etanol de segunda geração a partir de resíduos do processamento da mandioca - Martinez, Daiana Gotardo (2016)
Cassava (Manihot esculenta Crantz) in addition to being easy to cultivate a plant is considered the highest productivity calories and higher biological efficiency as a source of energy, presenting a high starch content. Some by-products are generated from the processing of cassava among them the brown bark, bark, disposal, the crueira, fiber, bran and bagasse or scanning. The cassava meal is characterized as a starchy source that can be converted into sugars for obtaining biofuel, this work aimed to produce ethanol from cassava processing this waste. This study was conducted in Cascavel / PR, were obtained waste in four different potato starch manufacturers, namely: starch manufacturer Home, starch manufacturer Starches New World, the starch manufacturer Novo Horizonte and MCR starches, there was analysis of chemical parameters of samples, starch content, sugar, pH, raw grease, moisture and ashes. For the process of obtaining the ethanol the samples were subjected to enzymatic hydrolysis using alpha-amylase and amyloglucosidases, they were then fermented and distilled. The samples were analyzed by mass spectrometry to verify the presence of ethanol. The samples showed high starch content about 60% on average, all acid had been adjusted with NaOH to the hydrolysis process. The solutions of one treatment, presented a de12,6% ethanol content, two treatment 48.5% and 53.3% treatment four Solving the three treatment presented a very different baseline standard solution being that his analysis becomes difficult, but by the spectral comparison between the solution treatment and the treatment with three one expected to be with concentrations close to each other, yielding a value of approximately 12% for three treatment. The cassava meal is a potential biomass for ethanol production, with a significant content of starch, and responding to efficiently process using hydrolysis and saccharification enzymes